2D Systems based Dynamic Iterative Learning Control Design with Experimental Validation on a 3D Crane Model. Issue 29 (2019) - Hladowski, Lukasz; Galkowski, Krzysztof; Rogers, Eric
Abstract: Iterative learning control can be applied to systems that repeatedly execute the same finite duration task. The distinguishing feature of this form of control action is that all data generated on a previous execution of the task is available to compute the control action for the next execution. This paper uses the 2D systems setting to design a dynamic controller, with particular emphasis on enhancing the controller with filters to suppress noise build up from execution to execution. The design is experimentally validated on a 3D crane laboratory based facility.